Measurement of top quark polarisation in t-channel single top quark production - (:unkn) unknown (SPRINGER, 2016)
A first measurement of the top quark spin asymmetry, sensitive to the top quark polarisation, in t-channel single top quark production is presented. It is based on a sample of pp collisions at a centre-of-mass energy of 8TeV corresponding to an integrated luminosity of 19.7 fb(-1). A high-purity sample of t-channel single top quark events with an isolated muon is selected. Signal and background components are estimated using a fit to data. A differential cross section measurement, corrected for detector effects, of an angular observable sensitive to the top quark polarisation is performed. The differential distribution is used to extract a top quark spin asymmetry of 0.26 +/- 0.03(stat) +/- 0.10(syst), which is compatible with a p-value of 4.6% with the standard model prediction of 0.44.
Keywords: Hadron-Hadron scattering (experiments); Top physics; LHC